Upgrade Skill Mengajar dengan Microteaching di Era Modern - Jesika Sabrina; Even Andreas Telaumbanua; Apryaldi Sianturi; Jhony F Suha Pasaribu; Zulkarnaen Lumbangaol; Rafika Ardilla; Pindah Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of technology and the dynamics of education in the modern era require educators to continuously improve their teaching competencies in adaptive and innovative ways. One effective approach to enhancing teaching skills is through microteaching. Microteaching is a training method that allows teachers to practice teaching skills on a small, focused, and structured scale. Through this process, educators can refine abilities such as delivering material, managing classrooms, utilizing learning media, and conducting reflective learning evaluations. In the modern era supported by digital technology, microteaching can be integrated with various online platforms, video recordings, and data-driven feedback to significantly improve the quality of learning. Therefore, the implementation of microteaching not only helps teachers enhance their professionalism but also promotes the creation of more effective, interactive, and relevant learning experiences aligned with the needs of today’s students.